THE EFFECT OF CONTEXTUAL TEACHING AND LEARNING (CTL) MODEL WITH THE ASSISTANCE OF 3-DIMENSIONAL POWERPOINT-BASED ANIMATION ON CRITICAL THINKING SKILLS SCIENCE OF CLASS V STUDENTS): PENGARUH MODEL CONTEXTUAL TEACHING AND LEARNING (CTL) DENGAN BANTUAN ANIMASI 3 DIMENSI BERBASIS POWERPOINT TERHADAP KETERAMPILAN BERPIKIR KRITIS ILMU PENGETAHUAN SISWA KELAS V) - Fenny Putriyani (Pendidikan IPA, FMIPA, UNP, 2023)
One of the important skills for students to improve is critical thinking skills because it can make it easier for students to master the material and apply it in everyday life. However, based on research results, PISA results, and the findings of the Ministry of National Education, it shows that elementary school students' critical thinking skills in science subjects are still low. This is because learning is still teacher-centered and stimulus in the form of appropriate learning media is not used during the learning process. As an alternative to overcome this problem, teachers can use a contextual learning model (Contextual teaching and learning, CTL) with the help of Powerpoint-based 3D animation learning media. In this study, researchers used quantitative methods with experimental research types and Non-equivalent Control Group Design. The population of this study were all fifth grade students in Cibogo Village. The sample of this study consisted of 38 students from class V SDN 1 Cibogo and class V SDN Ciburial. Class V at SDN Ciburial was designated as the experimental class and class V at SDN 1 Cibogo as the control class.